Pengaruh Brand Awareness, Brand Image, Kualitas Produk, Harga dan Promosi Terhadap Keputusan Pembelian Air Minum dalam Kemasan (AMDK) Merek AQUA ( Studi Kasus pada Masyarakat di Kecamatan Pandaan Jawa Timur ) - Dita Octavia; Rois Arifin; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study was conducted to determine and analyze the influence of Brand Awareness, Brand Image, Product Quality, Price and Promotion on the Purchase Decision of AQUA Brand Bottled Drinking Water (AMDK) (Case Study on Communities in Pandaan District, East Java). This research belongs to the type of explanatory research with a quantitative approach, which was conducted to determine and analyze the influence between variables. Ferdinand's theory was used to take a sample, ie the number of items x 5 so that a total sample of 115 people was found.To solve the problem in this research, using validity test, reliability test, normality test, multiple linear regression test, multicollinearity test, heteroscedasticity test. This study uses multiple linear regression analysis with the help of SPSS 25. The results of this study are that there is a simultaneous influence between Brand Awareness, Brand Image, Product Quality, Price and Promotion on the Purchase Decision of Bottled Drinking Water (AMDK) Brand AQUA (Case Study on Communities in Pandaan District, East Java). There is a partial influence between Brand Awareness, Brand Image, Product Quality, Price and Promotion on the Purchase Decision of AQUA Brand Bottled Drinking Water (AMDK) (Case Study on Communities in Pandaan District, East Java). Keyword : Purchase Decision, Brand Awareness, Brand Image, Product Quality, Price And Promotion